Agriculture and natural resources: Overview - Quisumbing, Agnes R. (International Food Policy Research Institute, 2003)
Much has been written about the importance of gender issues in designing and implementing agricultural evelopment projects (Cloud 1983; Alderman et al. 1994; Quisumbing et al. 1998). Part of this literature has been motivated by the important role that women play in food production, particularly in Sub-Saharan Africa (Boserup 1970; Dixon 1982; Gladwin and Macmillan 1989), as well as in the management of natural resources (Meinzen-Dick et al. 1997). A significant portion of this literature has also arisen because of the unintended consequences of agricultural development projects that were implemented without taking into account the different rights, resources, and responsibilities of men and women within the household (for example, Jones 1983; Dey 1985; Braun and Webb 1989).